2005
DOI: 10.1002/ijc.21505
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alcohol consumption and gene polymorphisms ofADH2andALDH2on hepatocellular carcinoma in a Japanese population

Abstract: Although alcohol intake as well as hepatitis viruses has been associated with hepatocellular carcinoma (HCC), gene-alcohol interactions on HCC risk remain to be elucidated. We conducted a case-control study to examine whether polymorphisms of alcohol dehydrogenase 2 (ADH2) and aldehyde dehydrogenase 2 (ALDH2) modified the HCC risk depending on the amount of alcohol intake. ADH2 and ALDH2 genotyping was performed by a duplex polymerase chain reaction with confronting two-pair primers in 209 newly diagnosed HCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 32 publications
7
60
0
Order By: Relevance
“…Traditional multivariate analyses in this study found significant association between alcohol drinking and hepatocellular carcinoma, with a greater than 2.5-fold OR, but did not show any direct association between hepatocellular carcinoma and the SNPs rs1229984 and rs671. Past studies examining the association between alcohol drinking and ADH1B/ALDH2 also did not find significantly increased risk for hepatocellular carcinomaamong drinkers with chronic liver disease or chronic HBV who carried at least one polymorphism (25)(26)(27).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Traditional multivariate analyses in this study found significant association between alcohol drinking and hepatocellular carcinoma, with a greater than 2.5-fold OR, but did not show any direct association between hepatocellular carcinoma and the SNPs rs1229984 and rs671. Past studies examining the association between alcohol drinking and ADH1B/ALDH2 also did not find significantly increased risk for hepatocellular carcinomaamong drinkers with chronic liver disease or chronic HBV who carried at least one polymorphism (25)(26)(27).…”
Section: Discussionmentioning
confidence: 88%
“…Only some studies have examined the association between these SNPs and the development of hepatocellular carcinoma, and results have been inconclusive, and either consisted of small sample sizes, did not control for confounding factors, or did not fully examine the interaction or mediation effects between these variants and alcohol drinking on hepatocellular carcinoma risk (25)(26)(27). Moreover, very few studies have studied these interactions among patients chronically infected with HBV (25).…”
Section: Introductionmentioning
confidence: 99%
“…The genes that encode these representative alcohol-metabolizing enzymes display polymorphisms that modulate individual differences in alcoholand acetaldehyde-oxidizing capacity [Bosron and Li, 1986;Marchand et al, 1999;Yokoyama et al, 2001]. Moreover, these individual differences in genes modify the risk of several type of cancers [Matsuo et al, , 2006aSakamoto et al, 2006;Yang et al, 2005;Yokoyama et al, 1998]. …”
Section: Introductionmentioning
confidence: 98%
“…Accumulating evidence suggests that a drinking habit for an individual with the ALDH2*2 allele increases the risk of cancerous diseases, including upper aerodigestive, gastric, colorectal, hepatic, and lung cancer [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. For example, it was reported that individuals with the ALDH2*1/*2 genotype who were heavy drinkers (C46 g ethanol/day and C5 days/week) had a 38-fold greater risk of developing oesophageal cancer compared to non-drinking individuals with the ALDH2*1/*1 genotype, while drinkers with the ALDH2*1/*1 allele had only a 2-fold greater risk [47].…”
Section: Effect Of Aldh2*2 On Cancerous Diseasesmentioning
confidence: 99%